2013
DOI: 10.1002/0471140864.ps2907s74
|View full text |Cite
|
Sign up to set email alerts
|

Methods for Studying Interactions of Detergents and Lipids with α‐Helical and β‐Barrel Integral Membrane Proteins

Abstract: Methods for studying interactions of protein with lipids and detergents are described for representatives of two major classes of membrane proteins: (1) the α-helical heterooligomeric integral cytochrome b6f complex of oxygenic photosynthesis from cyanobacteria, and (2) the outer membrane β-barrel proteins BtuB and OmpF from Gram-negative Escherichia coli bacteria. Details are presented on the use of detergents for purification and crystallization of the b6f complex as well as a method for lipid exchange. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…1B). These spectra are consistent with the well-documented precedent for the spectrum for light-induced oxidation of cytochrome f (Cramer and Hasan, 2016; Hasan et al, 2018), and also provide a spectrophotometric reference for the additional studies reported here on the amplitude and kinetics of the light-induced redox turnover of b-cytochromes in intact cyanobacteria. The amplitude and time course of 'dark reduction,' the redox change in the dark to light-induced oxidation of cytochrome f in spinach thylakoid membranes, measured by the absorbance change at 554 nm relative to a reference change measured at 540 nm, is shown (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1B). These spectra are consistent with the well-documented precedent for the spectrum for light-induced oxidation of cytochrome f (Cramer and Hasan, 2016; Hasan et al, 2018), and also provide a spectrophotometric reference for the additional studies reported here on the amplitude and kinetics of the light-induced redox turnover of b-cytochromes in intact cyanobacteria. The amplitude and time course of 'dark reduction,' the redox change in the dark to light-induced oxidation of cytochrome f in spinach thylakoid membranes, measured by the absorbance change at 554 nm relative to a reference change measured at 540 nm, is shown (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Synechococcus sp. PCC 7002, wild-type, were grown in medium A (Hasan et al, 2018) under optimal growth conditions, 38°C with an incident light intensity of 100-150 micro Einsteins•m − 2 •s − 1 in 2% (v/v) CO 2 /air. The cell titer was assayed using a Cary 3 spectrophotometer through the optical density of the cell culture measured at 660 nm relative to that at a reference wavelength of 730 nm, using a spectrophotometer with the light collection and detector geometry designed for a high e ciency of collection of light scattered from the turbid cell suspension.…”
Section: Methodsmentioning
confidence: 99%
“…Orwick‐Rydmark, Arnold, & Linke () presents an extensive review of detergent diversity and focuses on their uses for MP solubilization. Additionally, Saif Hasan et al., () presents a case study that discusses specific strategies for selecting a detergent for purification and crystallization of two different integral MP complexes. Briefly, detergents are amphipathic molecules.…”
Section: Introductionmentioning
confidence: 99%